Composite dietary antioxidant index in relation to urge urinary incontinence in US men - Jin, Xuefeng; Tong, Wenhui; Sun, Li; Lu, Sujue; Xu, Tiantian; Sun, Pan; Liu, Yan; Li, Hangxu (Frontiers in Nutrition, 2024)
BackgroundUrinary incontinence (UI), particularly urge urinary incontinence (UUI), is a prevalent condition that worsens with age and negatively affects quality of life. Antioxidants, measured by the composite dietary antioxidant index (CDAI), have been linked to inflammation and other diseases, but their relationship with UUI remains uncertain. The purpose of this study is to investigate the relationship between UUI prevalence and CDAI.Materials and methodsData for this cross-sectional study were obtained from the National Health and Nutrition Examination Survey’s four cycles (2011–2018). The odds ratio (OR) and 95% confidence interval (95% CI) of the relationship between CDAI and male UUI were ascertained by the use of weighted univariate analysis, multivariate logistic regression, restricted cubic spline regression, and subgroup analysis. PSM and sensitivity analyses were performed to assess the robustness of the findings.ResultsA total of 7,735 participants took part in this study. After adjusting for potential confounders, CDAI was found to be negatively associated with the prevalence of UUI in those with lower CDAI (about half overall). This relationship lost significance in populations with higher CDAI. The negative correlation between zinc and the prevalence of UUI was more significant in populations with low antioxidant diets. The results remained consistent, with subgroup analyses finding a significant interaction effect for race only after PSM (p = 0.043), with no significant interaction effect observed for the rest.ConclusionThis study showed a negative correlation between CDAI and UUI incidence in the group of men with low CDAI levels (about half of the population). Thus, effective prevention or treatment of UUI requires dietary changes aimed at the male population with poor antioxidant diets.